ChemInform Abstract: Catalytic Asymmetric Aza‐Diels—Alder Reactions: The Povarov Cycloaddition Reaction. Issue 15 (15th April 2014) - Fochi, Mariafrancesca; Caruana, Lorenzo; Bernardi, Luca
Abstract Review: 86 refs.